PENDIDIKAN KESEHATAN DENGAN METODE SYNDICATE GROUP MENINGKATKAN PENGETAHUAN TENTANG PENCEGAHAN ISPA PADA REMAJA PUTRI DI PONDOK PESANTREN - Dian Naelatul Karimah; Ninuk Dian Kurniawati; Laily Hidayati (Universitas Airlangga, 2019)
Intoduction: Health education was one of nursing interventions that aimed to change behavior in increasing health status that can be done with syndicate groups discussion learning method. This study was aimed to examine influence of syndicate groups method about ARIs prevention in changing female adolescence’s knowledge and attitude at Amanatul Ummah Educational Institution, Mojokerto.Methods: This study was a quasy-experiment using pretest-posttest controlgroup design. Population was adolescence of Nurul Ummah Boarding School (20 respondents) as the treatment group and adolescence of Amanatul Ummah Boarding School (20 respondents) as the control group, which taken according to simple random sampling. Knowledge and attitude as dependent variables and syndicate groups method as independent variable. Data were collected by using questionnaire then analyzed with level of significance p<0.05 by Wilcoxon sign rank test and Mann Whitney test.Result: Syndicate groups method had effect on knowledge but not on attitude.Wilcoxon test of knowledge for treatment group showed p=0.001, where Mann Whitney posttest showed p=0.000. Otherwise, Wilcoxon test of attitude for treatment group showed p=0.655, where Mann Whitney posttest showed p=0.348.Discussion: The conclusion is health education with syndicate groups method about ARIs prevention in boarding school can increase the level of knowledge but there is no significant change in attitude. Researcher believes that there were other factors that influenced the attitude posttest results, such as: factors of respondents; factors offacilitators, and; weaknesses of the implementation process and method of syndicate groups.